THE EFFECTIVENESS OF GUIDED WRITING TECHNIQUE IN TEACHING WRITING REPORT TEXT - Deviani, Dionesia; Suhart, Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know whether or not it is effective to use of Guided Writing Technique in teaching writing report text. This research was applied to a written test before and after the treatments. The researcher applied pre-experimental design. The population of this research were all of the second year students of Don Bosco Senior High School Sanggau in academic year 2017/2018 and the sample was taken from the second year of science students which consists of 38 students. The data was analyzed by using t-test and effect size formula. The finding showed that, the studentsâ€™ mean score of posttest is 76 that was higher than the studentsâ€™ mean score of pre-test that is 55.2. On the other hand, the findings also showed that t-test is 10.13 was higher than t-table that is 1.697, while the effect size is 1.64 and categorized as strong effect. In conclusion, the use of Guided Writing Technique is effective in teaching writing report text. Therefore, the alternative hypothesis which stated â€œGuided Writing Technique is effective to teach writing report text to the second year of science students of Don Bosco Senior High School Sanggau in Academic Year 2017/2018â€ was accepted.Â Keywords: Guided Writing Technique, Teaching Writing, Report Text, Pre-Experimental Study Â